Bias Budaya Minuman Beralkohol: Kajian Komunikasi Antar Budaya Perpsektif Agama Dan Budaya - Muhammad Hilmy Aziz (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Indonesia's culture allows for a wide range of customary and religious cultural practices. Alcoholic beverages are one of the products of a combination of culture and customs. This article examines the biases inherent in artistic labeling and the legality of consuming alcoholic drinks despite their traditional production process. It cannot be denied that the ideology of Pancasila has the highest position, namely the supreme deity, which can be interpreted as a form of primary guidance in implementing the state from upstream to downstream. The primary purpose of this article is to provide a religious and cultural study that discusses the bias that has been a conflict between government regulations regarding the consumption of alcoholic beverages and traditionally processed alcoholic drinks. A qualitative meta-synthesis approach centered on systematic qualitative review produces a holistic study and assessment of religious and cultural perspectives. The results of this study, firstly that from a spiritual perspective, Indonesia is the nation with the largest Muslim population in the world, meaning that it is predominantly Muslim, which signals that all forms of intoxicating drinks are a form of prohibition in religion and this is also contrary to the ideology of Pancasila which upholds divinity. Secondly, no culture would ever justify the consumption of alcoholic beverages that have a variety of negative impacts, both in terms of health and social aspects.